1988
DOI: 10.1037/0096-3445.117.3.258
|View full text |Cite
|
Sign up to set email alerts
|

Strategy choice procedures and the development of multiplication skill.

Abstract: Many intelligent strategy choices may be accomplished through relatively low-level cognitive processes. This article describes a detailed model of how such "mindless" processes might lead to intelligent choices of strategies in one common situation: that in which people need to choose between stating a retrieved answer and using a backup strategy. Several experiments testing the model's applicability to children's single-digit multiplication are reported. These include tests of predictions about when different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
597
2
17

Year Published

1990
1990
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 455 publications
(641 citation statements)
references
References 52 publications
25
597
2
17
Order By: Relevance
“…From both Logan's and Siegler's models (Logan, 1988;Siegler, 1988), one can expect that retrieval of prices in euros from memory would be more established for frequently bought items than for rarely bought items, the latter presenting a situation of higher uncertainty and more prone to bias. Jonas and Frey (2003) have recently shown that before the euro switch, the at the time unfamiliar currency caused decisions framed in euros to have more uncertainty and risk than the same decisions framed in DM.…”
Section: Discussionmentioning
confidence: 99%
“…From both Logan's and Siegler's models (Logan, 1988;Siegler, 1988), one can expect that retrieval of prices in euros from memory would be more established for frequently bought items than for rarely bought items, the latter presenting a situation of higher uncertainty and more prone to bias. Jonas and Frey (2003) have recently shown that before the euro switch, the at the time unfamiliar currency caused decisions framed in euros to have more uncertainty and risk than the same decisions framed in DM.…”
Section: Discussionmentioning
confidence: 99%
“…For the final interpretation of the results of this study consider Siegler's (1988b) recent argument that adaptive strategy choices are "part and parcel of the system's basic retrieval mechanism" (p. 272). An implication of Siegler's argument is that the use of backup strategies might not require conscious "mindful" self-regulation or metacognition.…”
Section: Discussionmentioning
confidence: 99%
“…An adaptive strategy choice is likely a function of two variables: (a) the probability of alternative strategies producing the correct answer combined with (b) the relative duration of these alternative strategies. To illustrate, memory retrieval will nearly always produce the shortest solution time, relative to the backup strategies, but retrieval is an adaptive strategy choice only if the obtained answer is likely to be correct (Geary & Burlingham-Dubree, 1989;Siegler 1988aSiegler , 1988b). Otherwise, an adaptive strategy choice would require the execution of a more time consuming but more accurate process, such as counting on fingers (Siegler, 1986).…”
Section: Strategy Choicesmentioning
confidence: 99%
“…Retrieval latency and procedural latency were regressed on the same three variables and on percentage retrieval use as well. Doing so, we wanted to test Siegler's (1988) prediction that retrieval frequency should correlate with retrieval eYciency but not with procedural eYciency. Indeed, both retrieval frequency and retrieval eYciency are in his model of strategy choice dependent on the peakedness of problem-answer associations, whereas procedural eYciency depends on the diYculty of executing the particular procedure.…”
Section: Regression Analysesmentioning
confidence: 99%